Aeolian mobility in the Middle São Francisco Dune Field, Northeast Brazil, as a response to Caatinga's droughts and land-use changes - Santos, Landerlei A. [UNESP]; Latrubesse, Edgardo M. (Elsevier, 2021)
In the last decade, the semiarid northeast of Brazil (Caatinga biome) has experienced one of the most prolonged and most severe droughts ever recorded in regional history. The study of the landscape changes contributes to understanding the environmental, social, and economic consequences of extreme climate events in the region. Here, we investigate the marginal area of the Middle São Francisco dune field, where in recent years, aeolian landforms development and their migration have been observed. To map the migration line of the aeolian front, we used 2002–2019 high-resolution images, from which we estimate the migration rates and evaluate the monthly migration rates for several interannual intervals, particularly during the drought peaks. In the area of greatest migration, the dunes advanced 210 m in 18 years. In the first decade, under climatic conditions closer to the historical average, dunes migrated ~15 m/y, while in the second decade, they migrated 80 m at a rate of 9.4 m/y. Examining the ranges of intra-annual migrations, we estimate that the highest mobility rate was almost five times greater than the rate at the end of the decade. In addition, we calculated a dune mobility index and the dune's morphological patterns. We conclude that the morphodynamic processes of dune formation and migration were triggered mainly by vegetation removal from river banks. The more severe climatic conditions during the last drought (2012–2017) enabled the dunes to migrate relatively quickly. The last few years (2017–2019) were marked by a considerable reduction in aeolian mobility and stabilization of expansion margins, inducing the formation of barchan-parabolic dunes.
Keywords: Aeolian dunes; Aeolian remobilization; Anthropogenic impacts; Desertification/aridization; Northeast Brazil; São Francisco River